Going Global: Differential Accumulation and the Great U-turn in South Africa and Israel - Jonathan Nitzan; Shimshon Bichler (Review of Radical Political Economics, 2001)
This paper offers a new theoretical approach for comparing the current political-economic U-turns in South Africa and Israel. Our principal focus is on a revised notion of capital, emphasizing the central role of differential accumulation by dominant capital groups. We further distinguish between an antagonistic “depth” regime in which differential accumulation is achieved via stagflation, and a less conflictual “breadth” regime where redistribution occurs through growth. Within this framework, we argue that both the recent transition in the two countries, as well as their former regimes, were greatly affected by global developments. Until the 1980s, accumulation in both countries depended largely on depth, characterized by a marked disparity between deepening crisis on the one hand, and rapid differential accumulation on the other. In South Africa, the large companies benefited disproportionately from the impact on gold profit of global inflation, and were therefore reluctant to abandon apartheid. Similarly, Israel's leading firms recorded spectacular gains riding the global arms race and regional conflict, and hence voiced little opposition to the continuation of a war economy at home. Recently, however, these global forces went into reverse, triggering in both countries a shift from depth to breadth. The disinflation associated with rapid globalization undermined gold profit in South Africa, while the end of the Cold War pulled the rug from under the global arms race, drying up the flow of war profit in Israel. In these new conditions, dominant capital groups in the two countries can sustain their differential accumulation only by investing outside their own borders. Capital mobility, though, requires political-economic stability, hence the support of these groups for democracy in South Africa and to regional reconciliation in Israel.
Keywords: 330; Arms; accumulation; acquisitions; apartheid; capital; capitalism; centralization; competition; conflict; conglomeration; corporation; credit; crisis; debt; demographics; development; distribution; dual economy; elite; energy; finance; globalization; gold|